Cipasung Heritage Creative Hub: Innovation In Msme Development Based On Cultural Tourism And Agrotourism In Cipasung Village, Lemahsugih, Majalengka - Akhmad Hidayat Nurul Akbar; Siti Amirah Makarim (CV. SINAR HOWUHOWU, 2025)
This community service activity aims to develop the